Licensing of Communications Networks and Services: Case Study of Market Liberalisation in South Africa and the United Kingdom - Raffinetti, Carla (LINK Centre, University of the Witwatersrand (Wits), Johannesburg, 2015)
The article contrasts the regulatory regime for licensing telecommunications networks and services in South Africa with that of the United Kingdom, in order to illustrate how regulation can be used to restrict competition (South Africa) or facilitate entry into the market (the United Kingdom). The purpose of this article is to suggest possible areas for licensing reform in South Africa, which is currently in the process of reviewing its ICT policy framework. There are three areas where licensing policy can play a key role in promoting competition in the market: infrastructure and services; spectrum licensing; and pro-competitive regulation, which allows for additional licence conditions to be imposed on entities that hold significant market power (SMP). This paper addresses the first issue only (infrastructure and services), as an area that is easily capable of reform. Currently, the system for licensing networks and services in South Africa requires the pre-approval of the regulator to be granted before a licence is issued, which is unduly resource-intensive. This article advocates that South Africa adopt a system of general authorisations for the licensing of networks and services similar to that applied in the United Kingdom. Such an approach would free up the regulator to address other areas that have received insufficient regulatory attention to date, notably spectrum licensing and pro-competitive regulation, both of which fall beyond the scope of this article.
Keywords: licensing telecommunications networks, licensing reform, pro-competitive regulation, class licensing framework, general authorisation regime, telecommunications networks and services, South Africa, United Kingdom